Hydrothermal Synthesis of Carbon Dots Derived from Biomass: A Simple and Sustainable Approach - Turdini, Shopi; Mulyadi, Dikdik; Yuningsih, Lela Mukmilah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Carbon dots (CDs) are a class of carbon-based nanomaterials that have attracted significant attention in the field of nanotechnology due to their strong photoluminescence, biocompatibility, and ease of surface passivation. In recent years, biomass-derived approaches for CDs synthesis have become a primary focus, driven by the growing demand for environmentally friendly, cost-effective, and sustainable synthetic methods. This study aims to synthesize carbon dots (CDs) from molasses, a sugar-based biomass waste, using a simple hydrothermal method. Characterization results revealed that the synthesized CDs have an average particle size of 313.5 nm and retain surface functional groups such as –OH, –COOH, C=O, and C–H, which are essential for extended applications. The findings demonstrate that molasses can serve as a viable carbon source that not only supports the concept of green synthesis but also opens new opportunities for biomass-based CDs in sustainable applications, including environmental remediation, adsorbents, or macro-scale drug delivery systems suitable for mucosal or gastrointestinal routes. Moreover, this work contributes to the advancement of eco-friendly carbon-based materials.